Translation and implementation of the Australian‐led PCOS guideline: clinical summary and translation resources from the International Evidence‐based Guideline for the Assessment and Management of Polycystic Ovary Syndrome. (1st October 2018) - Teede, Helena J; Misso, Marie L; Boyle, Jacqueline A; Garad, Rhonda M; McAllister, Veryan; Downes, Linda; Gibson‐Helm, Melanie; Hart, Roger J; Rombauts, Luk; Moran, Lisa; Dokras, Anuja; Laven, Joop; et al.
Abstract: Introduction: We have developed the first international evidence‐based guideline for the diagnosis and management of polycystic ovary syndrome (PCOS), with an integrated translation program incorporating resources for health professionals and consumers. The development process involved an extensive Australian‐led international and multidisciplinary collaboration of health professionals and consumers over 2 years. The guideline is approved by the National Health and Medical Research Council and aims to support both health professionals and women with PCOS in improving care, health outcomes and quality of life. A robust evaluation process will enable practice benchmarking and feedback to further inform evidence‐based practice. We propose that this methodology could be used in developing and implementing guidelines for other women's health conditions and beyond. Main recommendations: The recommendations cover the following broad areas: diagnosis, screening and risk assessment depending on life stage; emotional wellbeing; healthy lifestyle; pharmacological treatment for non‐fertility indications; and assessment and treatment of infertility. Changes in management as a result of this guideline: Diagnosis:▪when the combination of hyperandrogenism and ovulatory dysfunction is present, ultrasound examination of the ovaries is not necessary for diagnosis of PCOS in adult women;▪requires the combination of hyperandrogenism and ovulatory dysfunction in young women within 8 years of menarche, with ultrasound examination of the ovaries not recommended, owing to the overlap with normal ovarian physiology; and▪adolescents with some clinical features of PCOS, but without a clear diagnosis, should be regarded as "at risk" and receive follow‐up assessment.Screening for metabolic complications has been refined and incorporates both PCOS status and additional metabolic risk factors.Treatment of infertility: letrozole is now first line treatment for infertility as it improves live birth rates while reducing multiple pregnancies compared with clomiphene citrate.